2012
DOI: 10.2174/156652412802480826
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide Inhibits Osteopontin Expression and Breast Tumor Growth Through Down Regulation of PI3 Kinase/Akt Signaling Pathway

Abstract: Breast cancer is one of the most common cancers among women in India and around the world. Despite recent advancement in the treatment of breast cancer, the results of chemotherapy to date remain unsatisfactory, prompting a need to identify natural agents that could target cancer efficiently with least side effects. Andrographolide (Andro) is one such molecule which has been shown to possess inhibitory effect on cancer cell growth. In this study, Andro, a natural diterpenoid lactone isolated from Andrographis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 0 publications
0
50
0
Order By: Relevance
“…The combination of androgarpholide and taxifolin inhibit proliferation and trigger apoptosis of breast cancer cells by disrupting microtubule dynamics and acitivating the spindle assembly checkpoint (SAC) (21). In other studies, androgarpholide alone can inhibit proliferation of breast cancer cells and non-small cell lung cancer (NSCLC) cells by downregulating the PI3K/Akt pathway (22,23). NSCLC cells also can be suppressed by androgarpholide through the HIF-1α pathway (24).…”
Section: Diterpenoidmentioning
confidence: 99%
“…The combination of androgarpholide and taxifolin inhibit proliferation and trigger apoptosis of breast cancer cells by disrupting microtubule dynamics and acitivating the spindle assembly checkpoint (SAC) (21). In other studies, androgarpholide alone can inhibit proliferation of breast cancer cells and non-small cell lung cancer (NSCLC) cells by downregulating the PI3K/Akt pathway (22,23). NSCLC cells also can be suppressed by androgarpholide through the HIF-1α pathway (24).…”
Section: Diterpenoidmentioning
confidence: 99%
“…Moreover, these agents exhibit several side effects and drug resistance [8,17,18]. Studies showed that Andrographolide (Andro), which is derived from Andrographis paniculata, act as an anticancer agent with less side effect and is able to target CSCs in multiple myeloma [19][20][21]. Our data demonstrate that Andro is able to eliminate CD133 + cells from melanoma and reduces the tumor growth.…”
Section: Commentarymentioning
confidence: 70%
“…AG has been reported to possess antitumor activity in various human cancer cell lines, including lung [40], hepatocellular carcinoma [41], breast [42], and colon [43] cancer cells. In this study, we investigated the antitumor effect of AG on human OS cells for the first time and showed that treatment with AG induces autophagy, but not apoptosis, in human OS cells.…”
Section: Discussionmentioning
confidence: 99%